Morphogenetic Sharks of Genus Carcharinus Traded at Southwest Aceh Fish Landing Sites - Asri Mursawal; Samsul Bahri; Sri Wahyuni; Hayatun Nufus; Rudi Hermi; Muhammad Ali Sarong (Jurnal Natur Indonesia, 2023)
Research on the types of sharks traded at the Southwest Aceh fish landing site was conducted in September 2022. The purpose of this study is to analyze the morphology and genetic analysis of sharks. Sampling uses purposive sampling techniques, for morphological analysis refers to shark identification books, while genetic analysis uses the Sanger method used at the sequencing stage. Morphological data analysis using Image-j software, for genetic analysis, using Mega 6 (Molecular Evolutionary Genetic Analysis). Morphological analysis was carried out at the Laboratory of Biosystematics and Marine Genetics, Faculty of Fisheries and Marine Sciences, Teuku Umar University. Genetic analysis was carried out at the Denpasar Biodiversity Laboratory, Bali. The results of this study found two species of sharks with a total of 8 individuals from the genus Carcharinus.